Civil disobedience : an American tradition - Perry, Lewis, 1938-2022 (Yale University Press, 2013)
The distinctive American tradition of civil disobedience stretches back to pre-Revolutionary War days and has served the purposes of determined protesters ever since. This stimulating book examines the causes that have inspired civil disobedience, the justifications used to defend it, disagreements among its practitioners, and the controversies it has aroused at every turn. Tracing the origins of the notion of civil disobedience to eighteenth-century evangelicalism and republicanism, Lewis Perry discusses how the tradition took shape in the actions of black and white abolitionists and antiwar protesters in the decades leading to the Civil War, then found new expression in post-Civil War campaigns for women's equality, temperance, and labor reform. -- Publisher website.